Assessment of dietary and genetic factors influencing serum and adipose fatty acid composition in obese female identical twins - Kunesová, Marie; Hainer, Vojtech; Tvrzicka, Eva; Phinney, Stephen D; Stich, Vladimir; Parízková, Jana; Zák, Ales; Stunkard, Albert J (Lipids, 2002)
Fourteen pairs of obese female monozygotic twins were recruited for a study of genetic influences on serum and adipose fatty acid (FA) composition. Following 1 wk of inpatient stabilization, fasting serum and adipose tissue obtained by surgical excision were analyzed by thin-layer and gas chromatography. Intrapair resemblances (IPR) for individual FA were assessed by Spearman rank correlation and by analysis of variance and were found in serum cholesteryl esters (CF), triglycerides (TG), and adipose TG. With two exceptions (CE linoleate and adipose eicosapentaenoate), these IPR were limited to the nonessential FA. Palmitate had significant IPR in four lipid fractions; in serum CE and adipose TG palmitate was strongly correlated with multiple measures of adiposity. In contrast to other lipid fractions, serum phosphatidylcholine (PC) FA had 12 [PR, of which 6 were essential FA including arachidonate (r = 0.76, P < 0.0005), eicosapentaenoate (r = 0.78, P < 0.0005), and docosahexaenoate (r = 0.86, P< 0.0001). The PC [PR could not be explained by analysis of preadmission 7-d food records. After dividing the pairs into two groups differing and nondiffering according to fat intake of individuals in the pair, there was no evidence of a gene-environment interaction between fat intake and FA composition. The IPR for nonessential FA indicate that there is active genetic control of either food choices or postabsorptive metabolic processing. The high level of IPR in the PC fraction in contrast to the other lipid fractions suggests strong genetic influence over selection of specific FA for this membrane fraction independent of diet.
Keywords: Obesity; dvojčata monozygotní; mastné kyseliny; tuková tkáň; estery cholesterolu; obezita; Adult; dospělí; Fatty Acids; triglyceridy; nemoci u dvojčat; dieta; lidé; Adipose Tissue; ženské pohlaví; Humans; Cholesterol Esters; Diet; Twins, Monozygotic; Triglycerides; Diseases in Twins; Female; lidé středního věku; Middle Aged